Electrophoretic deposition of selenium - Aksakal, B.; Boccaccini, A. R. (Elsevier Science Bv, 2012)
Selenium has been suggested for a number of applications in the biomedical field. In this study, electrophoretic deposition (EPD) of Se powder (100-mesh) was investigated to develop coatings with potential applications in orthopedic implants. Se powder was suspended in sulfuric acid and stable suspensions were obtained with addition of ethanol and distilled water. The film growth rate was varied by different deposition times in the range of 5 to 20 min at voltages of 1.5-3 V. The deposits were characterized qualitatively by bending strength tests, SEM observations and EDX analysis. Results of this study demonstrate that Se coatings can be readily obtained by EPD for the surface modification of metallic materials which is of potential interest in orthopedics and bone tissue engineering applications where Se can be useful as an anticancer agent. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Electrophoretic deposition; Selenium; Biomaterials; Coatings